(untitled) (Heritage, 2021)
During the Second World War, the connection between Belgrade and Zemun was very important for the illegal communist movement. In this way all reports, materials and money were sent to the Provincial Committee for Serbia. On the other hand, the Provincial Committee for Serbia used this connection to send letters to the District Committee of Zemun and to transfer compromised illegals to liberated territory. Maintaining this connection was quite difficult and dangerous because this was the border "between two states", which had to be crossed with appropriate IDs and often with various illegal materials. All illegals had to be provided with passports or appropriate IDs, which they procured illegally. In order to fulfill these tasks, the Communist Party recruited police officers who were sympathizers of the communist movement, as was the case with Cvetko Crnjak and his group. Cvetko Crnjak was a policeman who worked in the ship’s police in Zemun. He became a sympathizer of the movement even before the beginning of the Second World War, and from 1941 he began to actively cooperate with the movement. He did not work alone, but was assisted by his fellow police officers Simo Crnjanski, Ljubisa Topalovic and Sava Dragovic. Crnjak was involved in several party actions during the war: procuring weapons for the communist movement, spreading communist propaganda, transporting illegals, procuring false documents. In 1943, he was elected to provide the secretary of the Provincial Committee on the way to Leskovac. This whole group was discovered in October 1943. After that, Ljubisa Topalovic, Sima Crnjanski and Sava Dragovic were sent to camps abroad, and Cvetko Crnjak was shot in Marinkova bara on April 27, 1944. All of them were forgotten after the war, and the Communist Party did not in any way acknowledge their work.